'Cendekia Bitara Award 2012' - Noor Syahidah, Sabran (Penerbit UMP, 2013)

(untitled)
Universiti Malaysia Pahang (UMP)'s Research and Innovation Department (JP&I) organised the 'Cendekia Bitara Award 2012' on April 19, 2012.